Pengaruh Kekontrasan Optotype Snellen Terhadap Tajam Penglihatan Pada Pemeriksaan Refraksi Subjektif - Wahyu Budiana; Opep Cahya Nugraha; Zakaria Efendi (Jurnal Mata Optik, 2021)
The visual acuity examination is affected by the contrast between the background of the optotype used and the letter. Changes in contrast result in unstable visual acuity and affect the examination results subjectively. The writing of this paper uses a descriptive method using a variety of literature data, one of which is by David Cline, John R. Hofstetter and Henry W., Griffin, with the title. Dictionary Of Visual Science, Fourth Edition which explains that contrast in Snellen's optotype affects visual acuity.